Rare case of extra nasopharyngeal angiofibroma arising from tonsil-case report - Sankarapandian, Udhaya Sankaran; Ravindran, Hiran Kattilaparambil (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Angiofibroma is a highly vascular tumour. It occurs in adolescent males mainly in nasopharynx. Due to aggressive local growth, skull base location and risk of profound haemorrhage, management is challenging. Angiofibromas have been sporadically described in extra nasopharyngeal locations. Presentation varies depending upon the location of origin. Here we present a case of 7 year old boy presenting with difficulty in breathing with lump in the throat for 3 years, which has progressively increased in 4 months period with recurrent chocking while sleeping. Initially he was diagnosed with polyp arising from the tonsil. Polyp along with tonsil excised completely. Histopathology confirmed extra nasopharyngeal angiofibroma (ENA). To the best of our knowledge, only 3 cases arising from tonsil had been reported in English literature.